E-commerce and Market Penetration Strategies in Overcoming Geographical Challenges in Indonesia's Retail Industry - Bakri; Rochmah, Amanda Azizah Nur; Safitri, Enggi Anggreini; Indriani, Khofifah; Erlina, Siti Rohmah Agustina Dwi (PT. LITERASI SAINS NUSANTARA, 2024)
Indonesia is the world's largest archipelagic country, with over 17,000 islands spread along the equator. This geographical condition creates significant logistical challenges for the retail industry. The emergence of e-commerce as a new distribution channel offers hope to overcome these geographical barriers and open wider market access. This research will highlight the importance of e-commerce in addressing geographical challenges in Indonesia's retail industry. Through a comprehensive literature review, this study will identify successful strategies that have been implemented, as well as the challenges and opportunities present, with the aim of providing recommendations that can support sustainable and inclusive e-commerce development in Indonesia. The research employs a literature review method with a qualitative approach, utilizing data from Google Scholar for the period 2004-2024. The study's findings indicate that e-commerce has emerged as a potential solution to these barriers by leveraging digital technology, collaborating with logistics providers, and employing marketing strategies tailored to local needs. Through case studies of companies such as Tokopedia, Bukalapak, Blibli, and Shopee, it is evident that successful e-commerce in overcoming geographical challenges requires innovation, consumer trust, and government support. Strategies such as Bukalapak's Partner Program, JD.id's use of drones, and Shopee Guarantee feature demonstrate that Indonesian e-commerce companies can overcome various obstacles with creative and adaptive approaches.